An Empirical Investigation of Asset-Pricing Models in Vietnam - Diep, Thanh Tu (2009)
The main focus of this study is to examine the applicability of the most commonly used asset-pricing models in the context of Vietnamese stock market. The analyzed data are based on Bloomberg’s record of 35 listed stocks and VN-Index over the three-year period March 2006 through February 2009. This study ultimately aims at providing investors in Vietnam with a tool to support their investment decisions. Firstly, following both timeseries and cross-sectional methods employed by Fama and MacBeth (1973), this study documents that traditional Capital Asset Pricing Model (CAPM) fails to capture the variations of cross-sectional stock returns. Secondly, consistent with Pettengill et al. (1995), a significant conditional relationship between beta and realized return is observed when taking into account of positive and negative realized market excess returns. Thirdly, contrary to the findings of Chen, Roll and Ross (1986), this study shows there is no impact of macroeconomic factors, namely exchange rate, inflation rate, interest rate, and money supply on stock returns. Also, in the regression including these macroeconomic risk factors, the relation between beta risk and average realized return is still unable to be found. At last, the findings of this study generally support the three-factor model of Fama and French (1992) in which market factor, firm size and book-to-market ratio best describe the variations in cross-section of stock returns in Vietnamese equity market data. In short, the implication of this study for investors is that microeconomic factors such as firm size and book-to-market should be taken into account together with beta risk in any investment decision in the Vietnamese stock market.